Every nephron deserves a second chance before nephrectomy in obstructed uropathy due to urolithiasis. Issue 2 (May 2022) - Tonyali, Senol; Ortac, Mazhar; Dursun, Murat
Objective: In this case report, we aimed to present our clinical experience in a patient with hydronephrotic and atrophic kidney due to impacted lower ureteral stone. Case description: A 56-year-old male was admitted to our emergency department with flank pain and nausea. A computed tomography scan revealed a 3 cm stone at the distal ureter, causing severe hydroureteronephrosis. Right kidney parenchyma was extremely thin at the medial zone, and some parenchyma was apparent at the upper and lower poles. We planned renal scintigraphy, but it was impossible to perform quickly due to the active appointment list. The patient's kidney was assumed to be atrophic/non-functioning; however, given the long waiting list for renal scintigraphy and the patient's intractable pain, we decided to relieve the patient's pain with urinary drainage. Nephrostomy insertion was denied because of the extra thin parenchyma. About 40 days later, the patient underwent semi-rigid ureterorenoscopy under spinal anesthesia. It was impossible to place a double J stent to the ureter because of the kinked and extremely dilated ureter. So, we decided to place an open-end 6Fr ureter catheter. DMSA renal scintigraphy showed 33% right kidney and 67% left kidney function. Conclusion: Intractable flank pain might be a predictor of functioning renal parenchyma in hydronephrotic/atrophic kidneys. Renal split function lower than 10% on DMSA scintigraphy might not be an absolute indication of nephrectomy, especially in the obstructed renal unit. Evaluation of renal function after eliminating obstruction might be more reliable.